(untitled) (The Pakistan Development Review, 2009)
This study considers the importance of firm characteristics in explaining the degree of business constraints facing Pakistani firms in the Investment Climate Survey. We quantify how firms with differing characteristics experience particular problems. After controlling for other factors, the largest differences in responses to business constraints occur among firms that vary by manufacturing industry, and among firms operating under different ownership structures or selling in different markets. In some cases, firm size and firm location also play an important role. The age of the firm generally does not lead to significant differences. These results account for the heterogeneity of firms better than others, and may be important for policy-makers to develop more specific approaches to fostering the investment climate.